2020
DOI: 10.3390/cells9030580
|View full text |Cite
|
Sign up to set email alerts
|

Job Opening for Nucleosome Mechanic: Flexibility Required

Abstract: The nucleus has been studied for well over 100 years, and chromatin has been the intense focus of experiments for decades. In this review, we focus on an understudied aspect of chromatin biology, namely the chromatin fiber polymer’s mechanical properties. In recent years, innovative work deploying interdisciplinary approaches including computational modeling, in vitro manipulations of purified and native chromatin have resulted in deep mechanistic insights into how the mechanics of chromatin might contribute t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 121 publications
(139 reference statements)
0
5
0
Order By: Relevance
“…According to previous studies on Young's modulus across single and macromolecules, stiffness tends to decrease as DNA assembles into higher-order complexes from nucleosomes to chromosomes. 54 For example, the supercoiling structure of chromatin fibers could have a spring-like relaxation effect, and the DMT modulus value gradually decreases as chromosomes are formed. The inverse relationship of DMT modulus according to the hierarchical structure of chromosomes is very similar to that of steel wool.…”
Section: Resultsmentioning
confidence: 99%
“…According to previous studies on Young's modulus across single and macromolecules, stiffness tends to decrease as DNA assembles into higher-order complexes from nucleosomes to chromosomes. 54 For example, the supercoiling structure of chromatin fibers could have a spring-like relaxation effect, and the DMT modulus value gradually decreases as chromosomes are formed. The inverse relationship of DMT modulus according to the hierarchical structure of chromosomes is very similar to that of steel wool.…”
Section: Resultsmentioning
confidence: 99%
“…This structural reorganization of chromatin stores and dissipates mechanical energy constituting the main source of internal nuclear force, exerting a consequent pressure on the nuclear envelope. 3,4 Previously, we showed that chromatin decompaction was correlated with an increase in the structuration of focal adhesions in human colon cancer cells. This chromatin decompaction phenomenon was stimulated either mechanically by tuning the stiffness of the soft microenvironment or chemically by inhibiting histone deacetylase.…”
mentioning
confidence: 99%
“…34−36 The viscoelastic compliance of chromatin allows it to store and dissipate internal nuclear force modulating the pressure on the nuclear envelope. 4,37 Previous studies have also demonstrated that a significant amount of force, typically on the order of nanonewtons, is required to induce notable deformation of the nuclei of adherent mammalian cells. 38,39 The interplay between cytoskeletal forces and chromatin, along with focal adhesions, 40 collectively shapes nuclear morphology, and disruptions in any of these components 33 can lead to nuclear shape dysfunction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This could be the result of 'maturation' of initially liquid droplets to more dense gels or solids, which will alter the material properties of the condensate 30 . In the cell, the degree of long range chromatin contacts needs to be regulated as there is both a requirement for liquid like properties to allow access for diverse protein machineries 115 , as well as a need for structural support of the nucleus through dense chromatin domains 139,140 . b C-terminal domain.…”
Section: Linker Histone In Chromatin Phase Separationmentioning
confidence: 99%